O conselho de direitos da criança e do adolescente no município de Cariacica : discutindo as prioridades do financiamento - Marchesi, Elisângela Maria (2008)
It addresses the social policy for children and adolescents, having been chosen as the cut to analyze Municipal Council Rights of the Child and Adolescent of Oakdale (Comdcac), municipality of the state of Espírito Santo. It ponders the role of advisers in defining priorities and in the funding of the policies for children and adolescents, considering the heterogeneous composition relative to those advisers. Note that the 1980s is marked by a period of strong mobilization of social movements, triggering the process of re-democratization of the Brazilian state. This process of mobilization enacted the Federal Constitution of 1988 that brought new forms of dialogue between public authorities and civil society, inclusive in dealing innovating social policies. Social policy became the duty of the state and the right of the citizen. In 1990, when it enacted the Statute of the Child and Adolescent (Ecriad), children and adolescents were considered subjects of rights and absolute priority in their actions. At the same time, it regulated the establishment of Councils of Rights of the Child and Adolescent, as well as the creation of the Infancy and Adolescent Funds, a mechanism which aims to ensure the resources for policy execution, beyond the assurance that the priorities listed by the mentioned councils are not subordinated to the release of resources from the public power, since the resources that comprise the funds are managed directly by the councils. What was proposed is to give greater autonomy to the councils and also transparency to policy financing. Although these spaces have been installed since 1991 throughout the Brazilian territory, their action still shows incipient in the control of social policies. The ignorance about the role of the adviser presents itself as one of the biggest obstacles to the realization of these spaces. It is worth believing in the strong role of organized civil society in the process of building participative democracy. However, it is equally important that there are other spaces for participation. It is also necessary to expand the discussion on the roles of civil society in areas such as the Councils of Rights.